Job Satisfaction and Preference for Public Employment - Gamero-Burón, Carlos; García-Crespo, María Dolores (Springer, 2025)
This paper aims to identify the factors why the working population declares its preference for public jobs. For this objective, we use microdata from a nationally representative Spanish survey and include overall job satisfaction and job facets satisfaction in the current job and information on work values as additional regressors to explain why employees prefer to work in the public sector. The main result of our estimates is that the satisfaction variables are significant factors explaining the preference for public jobs. The empirical evidence also shows that women prefer public jobs more than men, regardless of their professional situation.
Keywords: Administración pública; Mujeres -- Trabajo; Política laboral; Job satisfaction; Gender; Public employment; Logit model